Venous thrombotic events in patients treated with immune checkpoint inhibitors for non-small cell lung cancer: A retrospective multicentric cohort study. Issue 205 (September 2021) - Deschênes-Simard, Xavier; Richard, Corentin; Galland, Loïck; Blais, Florence; Desilets, Antoine; Malo, Julie; Cvetkovic, Lena; Belkaid, Wiam; Elkrief, Arielle; Gagné, Andréanne; Hamel, Marc-André; Orain, Michèle; et al.
Abstract: Objectives: Venous thrombotic events (VTEs) are a frequent complication of non-small cell lung cancer (NSCLC) and are associated with increased morbidity. Immune checkpoint inhibitors (ICIs) are revolutionizing the management of NSCLC, but little is known about their impact on thrombosis. This study aims to define the incidence and clinical relevance of VTEs in NSCLC patients receiving these treatments. Methods: A retrospective multicentric cohort study including 593 patients from three centers in Canada and France was performed. The cumulative incidence of VTEs after ICIs was estimated using competing risk analysis, and the association of these events with survival and response to treatment was determined. Finally, univariate and multivariate tests were performed to identify VTE risk factors. Results: The cumulative incidence of VTEs in the cohort was 14.8% (95% CI = 7.4–22.2%) for an incidence rate of 76.5 (95% CI = 59.9–97.8) thrombosis per 1000 person-years, with most thromboses occurring rapidly after treatment initiation. VTEs were not correlated with overall survival, progression-free survival, or objective response to ICIs. Age ˂ 65 years old (HR = 2.00; 95% CI = 1.11–3.59) and tumors with PD-L1 1–49% (HR = 3.36; 95% CI = 1.19–9.50) or PD-L1 ≥ 50% (HR = 3.22; 95% CI = 1.21–8.57) were associated with more VTEs after 12 months of ICI initiation. Also, a delay of less than 12 months from diagnosis to the first ICI treatment (HR = 2.06; 95% CI = 1.09–3.89) and active smoking (HR = 2.00; 95% CI = 1.12–3.58) are probable risk factors of VTEs. Conclusion: This study suggests that the incidence of VTEs in NSCLC patients treated with ICIs is comparable to what is reported in other cohorts of patients treated with chemotherapy. In our cohort, VTEs were not associated with a decreased survival or response to therapy. Patient age < 65 and tumors with PD-L1 ≥ 1% were associated with a higher risk of VTEs under ICIs. Highlights: Venous thrombosis is common in NSCLC patients receiving immune checkpoint inhibitors. Comparable incidence of venous thrombosis under immunotherapy and chemotherapy No association between venous thrombosis and clinical response to immunotherapy Higher risk of venous thrombosis when age < 65 years and tumor PD-L1 ≥ 1% Likely higher risk of venous thrombosis if diagnosis <12 months and active smoking